Novel dual action chimera doxorubizen demonstrates superior efficacy to doxorubicin in acute leukemia - Dipak Walunj; Katarina Egarmina; Adi Zipin-Roitman; Siva Sai Naga Anurag Muddineni; Iryna Tkachenko; Pousali Mitra; Dror Tobi; Andrii Bazylevich; Ofer Shpilberg; Michael Milyavsky; Oshrat Hershkovitz-Rokah; Gary Gellerman (Scientific Reports)
Abstract Modifying existing drugs to enhance their activity and reduce toxicity is a major focus of drug development. We developed a novel class of dual-action chimeric molecules for cancer therapy, linking known drugs to a DNA-methylating monomethyl triazene moiety (azene) via nucleophilic substitution. In-vitro screening of these chimeras on various leukemia cell lines identified a potent chimera, doxorubizen, a sequel of the known DNA intercalator and topoisomerase 2 (Topo-II) inhibitor doxorubicin (Dox) and azene. Molecular docking and dynamic simulations showed doxorubizen as a more potent Topo-II inhibitor than Dox as it binds to major grooves in DNA. Moreover, the monomethyl triazene portion is positioned favorably through tetracene core intercalation, potentially facilitating methylation at nearby guanine bases. Doxorubizen demonstrated significantly higher cytotoxicity, mitochondrial depolarization, DNA intercalation, and cell death than Dox. A Topo-II activity assay confirmed potent enzyme inhibition by doxorubizen. The mechanism of action of doxorubizen involves the inhibition of DNA repair in proximity to double-strand breaks by guanine methylation, enhanced mitochondrial depolarization, and increased apoptosis. Furthermore, in an acute leukemia xenograft model, doxorubizen significantly reduced the leukemia burden compared to Dox while preserving body weight and liver function. This work underscores the therapeutic potential of doxorubizen in leukemia treatment.